A dynamic model of a nonlife insurance company - Akan, Mustafa (Copernican Journal of Finance & Accounting, 2016)
A Dynamics model of a nonlife insurance company is developed. Goodwill representing the awareness of the company by the public and the perceived quality of its services, and the technical capability representing the ability of the company to calculate the risk premium of the risks it considers to accept, are two state variables. The level of investment in advertising and quality improvement, and investments in technical capability are determined optimally to maximize the discounted profits of the company over an infinite horizon. The technical capability elasticity of number of customers and the claim ratio are shown to be determining parameters affecting the optimal paths of investments. The stability of equilibrium points are also shown to be dependent on these parameters.